A study of attrition rates in mathematics and science in Quirino High School and its implications for curriculum development - Valdez, Priscilla Calingasan- 1942- (1977)
This is a study of attrition rates in the academic subjects in a public high school. Interviews were conducted in gathering the data. The study found out that high attrition rate in Mathematics and Science in Quirino High School is a problem. The research pointed out that the school administrators and teachers alike must recognize that attrition, not only in the two subjects but also in others, cannot be totally blamed on the students alone.